2022
DOI: 10.3390/antiox11101930
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Alpha-Lipoic Acid against 5-Fluorouracil-Induced Gastrointestinal Mucositis in Rats

Abstract: Alpha-lipoic acid (ALA) is extensively utilized in multivitamin formulas and anti-aging products. The purpose of this study was to investigate the potential protective benefits of ALA on 5-fluorouracil (5-FU)-induced gastrointestinal mucositis in Wistar albino rats. Tissues from the stomach, small intestine, and large intestine were excised, and blood sera were obtained to identify biochemical indices such as TNF-α, IL-1β, MDA, GPx, SOD, MMP-1, -2, -8, and TIMP-1. A histopathological study was also performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…These factors may even be expected to become promising typical biomarkers to detect the severity of some lung diseases [238] . Ceylanlı et al [243] found that LA could suppress MMP-1, MMP-2, MMP-8, tissue inhibitors of metalloproteinase-1 (TIMP-1), TNF-α, IL-1, and MDA expression, thereby attenuating 5-fluorouracil (5-FU)-induced gastrointestinal mucositis in rats. In addition, LPS-induced high levels of MMP-1, MMP-2, TNF-α and IL-1β in the serum and pulp tissues were reduced following LA treatment [164] .…”
Section: The Mechanism By Which La Ameliorates Respiratory Diseasesmentioning
confidence: 99%
“…These factors may even be expected to become promising typical biomarkers to detect the severity of some lung diseases [238] . Ceylanlı et al [243] found that LA could suppress MMP-1, MMP-2, MMP-8, tissue inhibitors of metalloproteinase-1 (TIMP-1), TNF-α, IL-1, and MDA expression, thereby attenuating 5-fluorouracil (5-FU)-induced gastrointestinal mucositis in rats. In addition, LPS-induced high levels of MMP-1, MMP-2, TNF-α and IL-1β in the serum and pulp tissues were reduced following LA treatment [164] .…”
Section: The Mechanism By Which La Ameliorates Respiratory Diseasesmentioning
confidence: 99%
“…However, the agreed-upon hypothesis suggests that it consists of five stages: initiation, primary damage response, signal amplification, ulceration and healing 5,13,14 . Chemotherapeutics cause an imbalance of the redox system, resulting in an increased expression of reactive oxygen species 10 . These free radicals stimulate the second phase upregulating pro-inflammatory cytokines such as tumour necrosis factor (TNF)-α and interleukin (IL)-6 4,9▪▪ .…”
Section: Pathogenesis Of Gastrointestinal Mucositismentioning
confidence: 99%
“…The most significant predicament with GM is the need for more effective treatment; even with multiple potential therapeutics, an effective treatment regimen is yet to be approved by the United States Food and Drug Administration [1,2]. The lack of curative therapies and the severe symptoms of GM cause a significant negative impact on the quality of life of cancer patients [3,10]. Further investigation of the pathogenesis of GM, including immunoregulatory pathways that may provide therapeutic targets, is needed to fully elucidate the complex mechanisms and potential solutions for preventing or treating GM.…”
Section: Introductionmentioning
confidence: 99%
“…TIMPs bind to MMPs in a unidirectional manner, exerting inhibitory effects. Consequently, the balance between MMP and TIMP levels becomes a critical determinant of MMPs' efficacy in maintaining tissue homeostasis (6,7). Caspases serve as the principal executors of apoptosis, and numerous studies have demonstrated their involvement in MTX-induced tissue injuries, including oral and hepatorenal tissues (8,9).…”
Section: Introductionmentioning
confidence: 99%